The Utilization of Adaptive Digital Platforms in Social Studies Learning to Improve Social Literacy of Elementary School Students - Huriyah, Huriyah; Khairunnisa, Khairunnisa; Mahmudah, Mahmudah (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze the effectiveness of using adaptive digital platforms in Social Science (IPS) learning to improve the social literacy of elementary school students. Although digital technology is increasingly used in education, social studies learning in Indonesia is still teacher-centric and does not accommodate diverse learning needs. This study examines how adaptive platforms like Google Classroom can strengthen students' empathy, cooperation, and civic awareness. The study used a mixed-methods sequential explanatory design involving 60 grade V students from two elementary schools in South Kalimantan. Quantitative analysis using paired-sample t-test and ANCOVA showed a significant increase (p < 0.05) in all dimensions of social literacy, with the highest Increase in empathy (18%), followed by cooperation (15%) and civic awareness (12%). Qualitative findings from interviews and observations show that adaptive digital learning encourages active engagement, collaboration, and reflective communication among students. Adaptive platforms also create learning environments that are inclusive and responsive to individual learning styles, thus not only improving academic outcomes but also shaping social character and digital ethics. Theoretically, this research expands the application of social constructivism theory in the context of adaptive digital learning by placing social interaction at the core of the formation of social literacy in the 21st century. The results of this study provide practical implications for teachers, curriculum developers, and researchers to integrate adaptive technology in social studies learning to foster empathy, cooperation, and social responsibility in the digital era.